Influence of Salinity Stress on Color Parameters, Leaf Pigmentation, Polyphenol and Flavonoid Contents, and Antioxidant Activity of Amaranthus lividus Leafy Vegetables - Md. Nazmul Hossain; Umakanta Sarker; Md. Sharif Raihan; Asma A. Al-Huqail; Manzer H. Siddiqui; Shinya Oba (Molecules, 2022)
This is the first attempt to evaluate the impact of four salinity levels on the color parameters, pigments, polyphenols, flavonoids, and antioxidant capacities of four promising A. lividus genotypes. The color parameters, such as the yellowness/blueness (b*) and the chroma (C*); the antioxidant components, such as the polyphenols and flavonoids; and the antioxidant capacities of the leaves were remarkably increased by 39, 1, 5, 10 and 43%, respectively, at 50 mM of NaCl, and by 55, 5, 60, 34, 58 and 82%, respectively, at 100 mM NaCl concentrations. The green tower and SA6 genotypes were identified as tolerant varieties. The total phenolic content (TPC) and the total flavonoid content (TFC) played vital roles in scavenging reactive oxygen species (ROS), and they would be beneficial for the human diet and would serve as good antioxidants for the prevention of aging, and they are also essential to human health. A correlation study revealed the strong antioxidant capacities of the pigments and antioxidant components that were studied. It was revealed that A. lividus could tolerate a certain level of salinity stress without compromising the antioxidant quality of the final product. Taken together, our results suggest that A. lividus could be a promising alternative crop for farmers, especially in saline-prone areas in the tropical and subtropical regions.